Cerebral amyloid angiopathy initially occurs in the meningeal vessels. Issue 6 (23rd August 2017) - Takeda, Shigeki; Yamazaki, Kazunori; Miyakawa, Teruo; Onda, Kiyoshi
Abstract : To clarify the frequency of CAA in the brain parenchyma and subarachnoid space (SAS), we counted sections of blood vessels showing positive staining for Aβ in the SAS, cerebral cortex (CC) and cerebral white matter (WM) using paraffin‐embedded sections of the frontal, temporal and occipital lobes. The specimens had been taken for routine neuropathological examination from the brains of 105 Japanese patients (aged 40–95 years) selected from among 200 consecutive patients autopsied between 1989 and 2015 at our hospital. We examined the anatomical ratios of blood‐vessel sections in the SAS relative to the CC in three selected CAA cases, and those of Aβ‐positive blood‐vessel sections in CAA cases. CAA was found in 53 of the 105 cases (50.5%), and the youngest patient affected was a 51‐year‐old man. The incidence of CAA increased with age. The anatomical ratio of blood vessel sections in the SAS relative to the CC was 1/3.70–1/4.37 (mean: 1/3.94). The ordinary CAA group, in which CAA was seen in both the SAS and CC, included 41 cases (77.4%). In 37 of these cases, the SAS/CC ratio of Aβ‐positive blood vessels was 1/0.05–1/0.66 (mean: 1/0.26), and in the other four cases the ratio was 1/1–1/1.5. In the ordinary CAA group, the SAS/CC ratio of Aβ‐positive blood vessels was smaller than the anatomical ratio. The meningeal CAA group, in which CAA was found only in the SAS, included 12 cases (22.6%). These patients ranged in age from their fifties to their nineties. There was no case in which CAA was limited only to the CC. We concluded that CAA initially develops in the meningeal blood vessels, and not in the cortical blood vessels. CAA in the WM was seen in 10 cases, not only in nine cases that were severe, but also in a mild case.